Quality Of Life Satisfaction Among Caregivers Of Schizophrenic Patients - Rahat Usman; Anum Haider; Zoobia Ramzan; Shafi Mansoori (KARACHI MEDICAL AND DENTAL COLLEGE, 2021)
Objective: This study is aimed to determine the Quality of Life (QOL) satisfaction among caregivers of schizophrenic patients attending Outpatient department of Psychiatry, Abbasi Shaheed Hospital, Karachi Medical and Dental College. Method: The cross-sectional study was conducted among 150 caregivers of Schizophrenic patients from November 2015 to March 2016 attending out patient department of Psychiatry, Abbasi Shaheed Hospital, Karachi Medical and Dental College, Pakistan. The Caregivers were intimate family members who had spent their significant time (at least 2 years) with the schizophrenia patients. The self administered WHO QOL-BREF (validated Urdu version) scale which has 26 items, was used to measure the Quality of Life (QOL). Quality of life Satisfaction was labeled as positive if QOL score was >75% of the total score. Result: Out of 150 patients, the mean age of the caregivers was 45.36 ± 3.85 years. Most of the caregivers 95 (63.3%) were males and had care giving role of father 49 (32.6%). Most of them were unsatisfied of their QOL, 81 (54%). While only 69 (46%)of the caregivers were satisfied with their QOL. Their QOLwas found to be significantly associated with age of the patient (p-value <0.00 1) and caregiver (p-value <0.002), employment status (p-value 0.040), monthly family income (p-value <0.001), presence of physical illness of caregiver (p-value <0.001) and his/her relationship with the patient (p-value 0.048). Conclusion: Majority of caregivers of Schizophrenia patients were not satisfied with their Quality of Life. However, there are certain sociodemographic factors such as the age of patient and caregiver, employment and economic status, relationship with the patient and presence of physical illness of caregiver which were found to affect their satisfaction with QOL. Hence focusing those factors in the management plan may improve caregiver's satisfaction level.